2018
DOI: 10.1080/15284336.2018.1459343
|View full text |Cite
|
Sign up to set email alerts
|

Raltegravir versus lopinavir/ritonavir for treatment of HIV-infected late-presenting pregnant women

Abstract: Background Late-presenting pregnant women pose a challenge in the prevention of HIV-1 mother-to-child-transmission. We compared the safety and efficacy of raltegravir and lopinavir/ritonavir for this population. Methods We did a single-center, pilot, open-label, randomized trial in Brazil (N = 44). We randomly allocated late-presenting HIV-infected pregnant women (older than 18 years with a plasma HIV-1 RNA >1000 copies/mL) to receive raltegravir 400 mg twice a day or lopinavir/ritonavir 400/100 mg twice a day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…A pilot study in 40 women demonstrated that initiation of raltegravir‐based therapy, compared to lopinavir/r‐based therapy, resulted in significantly more women with undetectable viral load <50 HIV RNA copies/mL at delivery and a faster median time to viral load reduction to <50 HIV RNA copies/mL of 44 days in the raltegravir arm and 69 days in the lopinavir/r arm . Adverse event incidence rates were also lower in the raltegravir arm.…”
Section: Current Issues In the Use Of Art In Pregnancy And Pregnanmentioning
confidence: 99%
“…A pilot study in 40 women demonstrated that initiation of raltegravir‐based therapy, compared to lopinavir/r‐based therapy, resulted in significantly more women with undetectable viral load <50 HIV RNA copies/mL at delivery and a faster median time to viral load reduction to <50 HIV RNA copies/mL of 44 days in the raltegravir arm and 69 days in the lopinavir/r arm . Adverse event incidence rates were also lower in the raltegravir arm.…”
Section: Current Issues In the Use Of Art In Pregnancy And Pregnanmentioning
confidence: 99%
“…RAL has been the most frequently used INI, with demonstrated utility in patients with late diagnosis in pregnancy due to its good placental transfer, as well as in pregnant women with resistant viruses to first-line drugs [2][3][4][5]10,11], being currently the preferred INI in pregnancy [3].…”
Section: Methodsmentioning
confidence: 99%
“…Mother-to-child transmission (MTCT) is the main way of HIV infection in childhood [1]. Despite the great advances in its prevention, especially in the treatment of pregnant women with antiretroviral therapy (AT), currently there is still ongoing perinatal transmission [2], mainly in children of mothers with poor viral load (VL) control during pregnancy or with late diagnosis [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-viral drugs such as Raltegravir, Lopinavir-Ritonavir, Maraviroc, Nel navir and Tipranavir were also screened for tracing possible interaction with M pro . Raltegravir (-7.2 kcal/mol) is an anti-retroviral drug, used along with other drugs to relieve the HIV infection [44]. Lopinavir-Ritonavir (-7.7 kcal/mol) is a combination of two medications; lopinavir and ritonavir, used to control HIV/AIDS infection [45].…”
Section: Adme Prediction and Molecular Docking Analysismentioning
confidence: 99%